2021
DOI: 10.1097/jnc.0000000000000297
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic, Psychosocial, and Clinical Factors Associated With Employment in Women With HIV in the United States: A Correlational Study

Abstract: Employment is a social determinant of health, and women living with HIV (WLWH) are often underemployed. This correlational study examined the socioeconomic, psychosocial, and clinical factors associated with employment among WLWH (n 5 1,357) and women at risk for HIV (n 5 560). Descriptive and inferential statistics were used to evaluate factors associated with employment status. Employment was associated (p # .05) with better socioeconomic status and quality of life (QOL), less tobacco and substance use, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…A correlational study with WLHIV in the United States compared a group of employed women with a group of unemployed women, and having a job was associated with better quality of life, better compliance with consultations and antiretrovirals, HIV viral suppression and less depressive symptoms, stress and anxiety (26) . As for anogenital lesions, the prevalence in this study was higher than that identified in a North American study, in which 27% of WLHIV had high-grade squamous intraepithelial lesions of the anus (27) .…”
Section: Characterization Of Women Living With Hiv According To Socio...mentioning
confidence: 99%
“…A correlational study with WLHIV in the United States compared a group of employed women with a group of unemployed women, and having a job was associated with better quality of life, better compliance with consultations and antiretrovirals, HIV viral suppression and less depressive symptoms, stress and anxiety (26) . As for anogenital lesions, the prevalence in this study was higher than that identified in a North American study, in which 27% of WLHIV had high-grade squamous intraepithelial lesions of the anus (27) .…”
Section: Characterization Of Women Living With Hiv According To Socio...mentioning
confidence: 99%
“…Um estudo correlacional com MVHIV nos Estados Unidos comparou um grupo de mulheres que tinham emprego com um grupo de mulheres desempregadas, e ter emprego foi associado com melhor qualidade de vida, melhor adesão às consultas e aos antirretrovirais, supressão viral do HIV e menos sintomatologia depressiva, estresse e ansiedade (26) . Quanto a lesões anogenitais, a prevalência neste estudo foi superior à identificada em um estudo norte-americano, em que 27% das MVHIV possuíam lesões intraepiteliais escamosas de alto grau do ânus (27) .…”
Section: Discussão Caracterização Das Mulheres Vivendo Com Hiv Segund...unclassified
“…It can be argued that these factors support general health, protect against affective disorders, and thus support neuroplasticity and neurocognitive reserve [12]. In a sample of 1933 women (35% employed full or part-time) from the Women's Interagency HIV Study (WIHS), those who were employed engaged in less alcohol, tobacco, and substance use, experienced better cognitive, psychological, and physical health, and also had higher socioeconomic status and better quality of life [3]. For the 1373 women with HIV, employment was associated with better HIV viral load suppression and improved adherence to HIV-care visits [3].…”
mentioning
confidence: 99%
“…In a sample of 1933 women (35% employed full or part-time) from the Women's Interagency HIV Study (WIHS), those who were employed engaged in less alcohol, tobacco, and substance use, experienced better cognitive, psychological, and physical health, and also had higher socioeconomic status and better quality of life [3]. For the 1373 women with HIV, employment was associated with better HIV viral load suppression and improved adherence to HIV-care visits [3]. Finally, given the relationship between cognition and employment reported here, another interpretation of this study could be that by improving cognitive functions, this may improve the ability to negotiate the environment, including the work environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation